Auditors and Corporate Governance: Evidence from the Public Sector - Mark Schelker (Center for Research in Economics, Management and the Arts (CREMA), 2008)
Corporate auditors review and evaluate financial statements. To enhance independence the selection process and mandatory auditor rotation requirements have been debated intensively. The available empirical evidence is not conclusive and suffers from serious endogeneity problems. We propose learning from the public sector in which auditors play a similar role and present empirical evidence on the impact of auditor term length and rotation requirements on government performance at the US State level. We find evidence indicating that relatively short as well as extended auditor terms have a negative, and rotation requirements have a positive effect on state credit ratings.
Keywords: G30; G34; M42; 330; corporate governance; auditor; mandatory auditor rotation; public auditor